Evaluasi Kinerja Stasiun Penguapan Ditinjau dari Efisiensi Penggunaan Uap di PT. PG Rajawali II, Unit PG. Sindang Laut Cirebon - Rika Wulandari; Lestari Hetalesi Saputri (Jurnal Pengelolaan Perkebunan (JPP), 2021)
The evaporation station has an important role in the sugar factory. This station aims to concentrate the sugar solution until it reaches its saturation point (Â± 60% Brix), so that the process of forming sugar crystals at the cooking station becomes easier. However, the evaporation station also contributes to the highest sucrose inversion compared other stations. Sugar solution (sucrose) is resistant to high temperatures, long periods of time, and low pH. Therefore, it is necessary to evaluate the evaporation station. To reduce the risk of sucrose inversion in the evaporation station, the sugar solution is heated in a pressure vessel (vacuum). Vacuum conditions can lower the boiling point of juice. Performance evaluation of evaporation station is measured by the total temperature drop (Î£Î”T). The temperature drop is influenced by the distribution of pressure and temperature in evaporation, as well as the evaporation rate. The values of the parameters are compared with the literatures. The standard for the value of Î£Î”T is 40, while the standard evaporation rate for the quadruple effect evaporation system with bleeding is 26 kg/(m2.hour). The results of the evaluation show that the highest Î£Î”T value is 40.96 and the evaporation rate is 24.5 kg/(m2.hour), so it can be concluded that the operational condition of the evaporation station at PG Sindang Laut Cirebon is quite good. The evaporation system is also quite efficient. However, the evaporation rate is still categorized as inefficient